Captivating news in Colombia - Aparicio, Juan P.,Jetter, Michael (IZA - Institute of Labor Economics, 2020)
What motivates kidnapping decisions by rebel groups? This paper studies news coverage of a proposed prisoner exchange program (the Acuerdo Humanitario; AH) in connection with FARC (Revolutionary Armed Forces of Colombia) kidnappings in the early 2000s. We propose that AH News nourished the FARC's expectations of such an agreement, thereby altering their actions. Empirically, to circumvent latent endogeneity, we access disasters in countries hosting large numbers of Colombians as exogenous variation crowding out AH News. We find AH News systematically shifted the FARC's attention away from financial kidnappings (hostage-taking for ransom purposes) to political kidnappings (hostages subject to a potential prisoner swap). Neither news slant (articles supporting the AH) nor informational content drive results – rather, an explanation consistent with agenda setting appears most plausible. Further, AH News led to (i) more FARC killings of politicians; (ii) fewer non-kidnapping-related FARC attacks; (iii) more governmental press releases; and (iv) fewer military attacks on the FARC. Overall, AH News shifted the FARC's and the government's conflict strategy towards de-escalation while limiting casualties, at least in the short run.
10419/227361
Keywords: Graue Literatur; agenda setting; media; kidnapping; terrorism; FARC